Electron diffraction tomography and X-ray powder diffraction on photoredox catalyst PDI. Issue 15 (20th March 2019) - Bodach, Alexander; Zhao, Haishuang; Liu, Nai-Wei; Alig, Edith; Manolikakes, Georg; Kolb, Ute; Fink, Lothar
Abstract : The crystal structure of photoredox catalyst PDI-iPr was determined by a combination of electron diffraction tomography and XRPD. Abstract : N, N -Bis(2, 6-diisopropylphenyl)-perylene-3, 4, 9, 10-bis(dicarboximide) (PDI-iPr) is starting to be widely used as a metal-free homogeneous photoredox catalyst. The crystal structure was determined by a combination of electron diffraction tomography and X-ray powder diffraction and further validated by DFT-D calculations. Surprisingly, the molecular geometry of PDI-iPr leads to voids in the packing.